Identification PMS1 and PMS2 as potential meiotic substrates of CDK2 activity. - Nathan Palmer; S Zakiah A Talib; Christine M F Goh; Kajal Biswas; Shyam K Sharan; Philipp Kaldis (PLoS ONE, 2023)
Cyclin dependent-kinase 2 (CDK2) plays important functions during the mitotic cell cycle and also facilitates several key events during germ cell development. The majority of CDK2's known meiotic functions occur during prophase of the first meiotic division. Here, CDK2 is involved in the regulation of meiotic transcription, the pairing of homologous chromosomes, and the maturation of meiotic crossover sites. Despite that some of the CDK2 substrates are known, few of them display functions in meiosis. Here, we investigate potential meiotic CDK2 substrates using in silico and in vitro approaches. We find that CDK2 phosphorylates PMS2 at Thr337, PMS1 at Thr331, and MLH1 in vitro. Phosphorylation of PMS2 affects its interaction with MLH1 to some degree. In testis extracts from mice lacking Cdk2, there are changes in expression of PMS2, MSH2, and HEI10, which may be reflective of the loss of CDK2 phosphorylation. Our work has uncovered a few CDK2 substrates with meiotic functions, which will have to be verified in vivo. A better understanding of the CDK2 substrates will help us to gain deeper insight into the functions of this universal kinase.